Energy consumption, prices and economic growth in Nigeria: Autoregressive distributed lag model analysis - Afaha, John Sylvester; Agbede, Samsindeen Ayodele (goodwood publishing, 2025)
Purpose: This study aimed to test the relationship between energy consumption, energy prices, and economic growth in Nigeria by examining the coefficients of various variables in a regression analysis. Research Methodology: This study uses regression analysis to assess the relationship between energy-related variables and economic growth in Nigeria, focusing on factors such as gas consumption, crude oil prices, fuel prices, and coal consumption. Results: The results indicate that certain energy-related variables, such as gas consumption, crude oil prices, and coal consumption, have significant impacts on economic growth in Nigeria. The coefficients of these variables show both positive and negative relationships with GDP growth rates. Conclusions: Energy consumption is a key driver of Nigeria’s economic growth, with short-run demand driven by GDP and long-run growth sustained by increased energy use, highlighting the critical need for stable energy policies and infrastructure development. Limitations: One limitation of this study is the potential for omitted variable bias or unobserved factors that could influence the results. Contribution: This study contributes to the understanding of how energy consumption and fuel prices affect economic growth in Nigeria, providing insights for policymakers, researchers, and stakeholders in the energy sector. Novelty: The novelty of this study lies in its detailed analysis of the specific effects of energy-related variables on economic growth in Nigeria, highlighting the importance of energy policies and consumption patterns in driving economic performance. This study also contributes to the literature on how energy costs affect Nigeria's energy use and economic growth.